(untitled) (Sebha University Conference Proceedings, 2024)
Hepatitis is a global health problem and the most common occupational risk among health-care workers, as they are at greater risk of infection, occupational exposure occurs when injected, contaminated needles are used, or directly when dealing with patients, as well as during the potentially contagious blood transfusion or blood products. The purpose of this study is to assess the immune response to the hepatitis virus vaccine among healthy personnel in the city of Sebha after receiving the vaccine. Blood samples were collected for anti-surface antibodies test ,A sample of 102 persons was taken (79.4%) for females, 21 (20.6%) for males. The results of the screening of anti-surface antibodies showed that 86.3% were positive, while 13.7% were negative after receiving the vaccine. From this study, we conclude that the vaccine response was effective at 86.3%, while a significant percentage of 13.7% did not show a response, and they need to be revaccinated or given a booster dose, Regarding the impact of gender on the immune response .statistical results indicated no significant differences between males and females. It was found that the lowest positive response rate was among those who received only one dose of the series, while the highest rate was in the group that received three doses. There were no significant differences between the number of doses and the positive samples, while the negative samples showed statistical significance with a p-value of 0.04. Therefore, we recommend completing the vaccination series for healthcare workers and monitoring their immune response by measuring the concentration of antibodies to the surface antigen.